2016
DOI: 10.32007/med.1936/jfacmedbagdad.v58i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical alteration in some Iraqi children with autistic spectrum disorder (ASD)

Abstract: Background: Autism spectrum disorder (ASD) is a general term for a group of complex disorders of brain development; these disorders have no single known cause, they are characterized, in varying degrees, by difficulties in social interaction, verbal and nonverbal communication and repetitive behaviors. Objective: The aim of the study was to evaluate different biochemical parameters in some autistic Iraqi children, and to compare the results with healthy children who matched with age, looking for any alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results in Table (4) showed a significant decrease in Fe, Cu, Ca , and Zn in the patients eating gluten compared with the healthy subjects at a probability level (p ≤ 0.05), as well as a significant decrease in Fe, Cu, Ca and Zn elements in Patients abstaining from eating gluten compared to healthy subjects at a probability level (p 0.05). The results in Table (5) showed a significant decrease in iron, and no significant difference in copper, calcium and zinc among healthy subjects whose age group ranged between (2-12) years compared with healthy subjects whose age group ranged between (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) year at a probability level (p 0.05).…”
Section: Determination Levels Of Some Mineral Elements In Blood Serummentioning
confidence: 93%
See 1 more Smart Citation
“…The results in Table (4) showed a significant decrease in Fe, Cu, Ca , and Zn in the patients eating gluten compared with the healthy subjects at a probability level (p ≤ 0.05), as well as a significant decrease in Fe, Cu, Ca and Zn elements in Patients abstaining from eating gluten compared to healthy subjects at a probability level (p 0.05). The results in Table (5) showed a significant decrease in iron, and no significant difference in copper, calcium and zinc among healthy subjects whose age group ranged between (2-12) years compared with healthy subjects whose age group ranged between (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) year at a probability level (p 0.05).…”
Section: Determination Levels Of Some Mineral Elements In Blood Serummentioning
confidence: 93%
“…Although celiac is known as an injury to the small intestine and results in malnutrition, in recent times this disease has been characterized as a disorder that occurs in the function of many systems in the human body, also the incidence of mental illness, depression and infertility is increased in patients with celiac disease [3] . In another study conducted on autistic patients in Iraq, it was found that three of the autistic cases also have celiac disease [4] The kidneys work to get rid of excess fluids and waste products through the urine, and to maintain a balance of salts in the blood, and to control blood pressure and regulate some of hormonal functions such as erythropoietin, activation of vitamin D [5] . There is a relationship between celiac disease and kidney disease , In one study conducted on 827 kidney patients, it showed that 54 of them had celiac disease [6].…”
Section: Introductionmentioning
confidence: 99%